Indigeneous Public Administration: A Review and Deconstruction of the Idea, Concept, and Theory of Government and Governance - Suripto Suripto; Torontuan Yeremias Keban; Sri Harjanto Adi Pamungkas (Jurnal Borneo Administrator, 2021)
Indigenous Public Administration (IPA) has attracted researchers' attention and awareness of the importance of developing contextual theory and practice of public administration, especially in developing countries such as Indonesia. IPA emerges in many developing countries since the concept, theory and practice of Western Public Administration (WPA) have failed to respond to local issues, and therefore WPA practice is considered irrelevant. Basically, IPA is a constructed concept to fill a vacant space that unoccupied by Western Public Administration (WPA). This descriptive qualitative study aims to explain and criticize the theory and practice of IPA and WPA. The data were gathered from books, journals, institution reports, regulations and other relevant writings of organizations, professionals, and academicians. The technique of data analysis was based on a data analysis spiral. It reveals that IPA applies to countries such as Indonesia and China. In both countries, the practice of IPA helps to overcome public issues concerning social, economic, and political. It is expected that the findings of this study will pave the way for developing both concept and theory of IPA and responding to more complex society and government's demands and needs.